Stock Prices: Exploring the Effects of the Debt-to-Equity Ratio and Earnings Per Share - Suryana, Asep; Susetyo, Dwinanto Priyo; Rifa'i, Asep Achmad (Jurnal Akuntansi dan Sistem Informasi, 2026)
This study examines the effect of debt-to-equity ratio (DER) and earnings per share (EPS) on stock prices in a company listed on the Indonesia Stock Exchange (IDX). The research applies a quantitative approach using secondary data from verified quarterly financial reports over eight years, consisting of 32 observation periods selected through purposive sampling. Data analysis includes classical assumption tests, correlation tests, and predictive power evaluation based on the R² model using EViews v.14. Hypothesis testing employs t-statistics and F-statistics at a significance level of 0.05. The findings reveal that DER negatively affects stock prices, while EPS has a positive and significant effect. Simultaneously, DER and EPS positively and significantly influence stock prices with moderate predictive power. These results indicate that the combination of DER and EPS reflects profit growth and effective risk management, which may enhance investor confidence and support stock price increases.